Exploring First-Generation College Students Leadership Behaviors and Actions during Intramural Sports - Milone, Joseph (Journal of Campus Activities Practice and Scholarship, 2021)
College graduates need to have specific leadership-related skills, behaviors, and traits when entering the workforce. Campus involvement is one way for students to develop such areas. Therefore, this qualitative study explored the self-reported leadership skills of first-generation college students who were actively participating in intramural sports. Twelve students from a 4-year public university in the Northeast were interviewed about the research-driven photographs they submitted depicting leadership skills they engaged in during intramural sports participation. Photograph captions and interviews were analyzed using Kouzes and Posner's (2014) leadership model. Findings revealed that students reported engaging in behaviors and actions aligned with the leadership practices described by Kouzes and Posner (2014). These findings can help inform the decisions campus recreation professionals make about the role leadership development plays in program offerings.
Keywords: First Generation College Students; Intramural Athletics; Leadership Qualities; Photography; Student Attitudes; Student Behavior; Student Leadership; dept.rec; peer-reviewed